2010
DOI: 10.1159/000321318
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Lymph Node Dissection Is an Independent Risk Factor for Postoperative Cancer Death in Patients Undergoing Surgery for Stage II Colorectal Cancer

Abstract: Background: Surgical resection is the most effective treatment for patients with stage II colorectal cancer (CRC). However, a few patients with early-phase CRC suffer postoperative cancer death. Aims: To investigate the risk factors for postoperative cancer death in patients who undergo surgery for stage II CRC. Methods: Prognostic significance was analyzed by χ2 test, univariate analyses, Kaplan-Meier analysis and log-rank test using clinicopathological factors from the database. Results: A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…As mentioned earlier, inadequate lymph node assessment can lead to understaging of patients and thus delay life‐saving adjuvant treatment. Multiple reports have shown that inadequate lymph node evaluation is correlated with shorter overall survival in CRC patients with or without metastatic lymph nodes . In particular, the small lymph nodes omitted during surgery might be metastatic.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, inadequate lymph node assessment can lead to understaging of patients and thus delay life‐saving adjuvant treatment. Multiple reports have shown that inadequate lymph node evaluation is correlated with shorter overall survival in CRC patients with or without metastatic lymph nodes . In particular, the small lymph nodes omitted during surgery might be metastatic.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that insufficient lymph node examination is associated with shorter overall survival in both node‐negative and node‐positive CRC patients 7–13. In 2007, Chang et al 27 published a comprehensive systematic review of 17 studies that examined lymph node recovery as it relates to CRC survival.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that insufficient lymph node examination is associated with shorter overall survival in both node‐negative and node‐positive CRC patients 7–13. The National Comprehensive Cancer Network, American Joint Committee on Cancer, and American College of Pathologists recommend the examination of at least 12 lymph nodes for adequate CRC staging 3, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic ability of pN may be influenced by the total number of lymph nodes removed and the pN classification requires a minimal number of retrieved nodes in order to prevent stage migration. 5 7 The ratio-based system (rN), representing the ratio of positive nodes to total retrieved nodes, has been proven to better predict outcomes than pN. 6 , 8 10 Our previous study validated the utility of rN utility in such major cancers as breast cancer, colorectal cancer, and HNC in Taiwan.…”
Section: Introductionmentioning
confidence: 99%